Challenges Faced by Islamic Higher Education Students in English Writing Classes: A Qualitative Approach - Amrizal, Amrizal; Setiawan, Anjar (Journal Corner of Education, Linguistics, and Literature, 2025)
This study looks at the challenges university students face in English writing classes at STAIN Mandailing Natal, Indonesia, using a qualitative approach. Writing is often seen as one of the hardest skills in English as a Foreign Language (EFL), especially at the university level, where students must produce academic texts. Although English academic writing is becoming more important in higher education, there has been little qualitative research on students’ writing challenges in Indonesian Islamic universities, particularly in regional areas.This study employed a descriptive qualitative design and included undergraduate students enrolled in English writing courses at STAIN Mandailing Natal. Data were collected through semi-structured interviews and students’ reflections on their writing experiences. Thematic analysis was used to find common patterns in students’ writing difficulties and their views on teaching practices.The findings reveal four major themes of challenges: linguistic challenges, cognitive and rhetorical challenges, affective challenges, and instructional challenges. Students reported difficulties in grammar usage, limited vocabulary, and sentence construction. They also struggled with organizing ideas, developing arguments, and maintaining coherence in academic writing. Affective factors such as writing anxiety, low confidence, and fear of making mistakes further hindered students’ engagement. In addition, students perceived that instructional practices and feedback were often insufficient to support their writing development. The study concludes that English writing challenges among Indonesian EFL university students are multidimensional and context-dependent. The findings suggest the need for more student-centered, process-oriented, and context-sensitive writing instruction. This study contributes to the EFL writing literature by providing empirical insights from an under-researched Islamic higher education context in Indonesia.